Pengembangan Bahan Ajar Interaktif Menggunakan Articulate Storyline 3 Pada Materi Kekayaan Budaya Indonesia - Luthfiyyah Salsabila; Dendy Saeful Zen; Yuli Mulyawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to investigate the development of interactive teaching materials using Articulate Storyline 3 to be implemented for fourth-grade students at SDIT As-salaam, as well as to assess the feasibility and effectiveness of these interactive teaching materials in the learning process conducted at the school. The research method used is Research and Development with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). In this study, validation tests were conducted by experts, including media experts, language experts, and two material experts. The validation results showed that the media expert gave a score of 100% with a very feasible category, the language expert scored 92% with a very feasible category, material expert 1 scored 90% with a very feasible category, and material expert 2 scored 98% with a very feasible category. Student response questionnaires obtained a score of 94% with a very feasible category, and the average N-Gain score of learning outcomes was 0.77 with a very high category. These results indicate that the interactive teaching materials using Articulate Storyline 3 are very feasible for use in the learning process and are highly effective in improving student learning outcomes.